In vitro antioxidant activity of eight wild edible plants in Bursa province of Turkey - (:unkn) unknown (Romanian Society for Pharmaceutical Sciences, 2016)
The antioxidant properties of ethanolic extracts from eight wild edible plants, which were collected in both fresh edible as vegetable and flowering (inedible) periods were investigated by employing various established in vitro systems: DPPH free radical scavenging, ABTS radical cation scavenging and metal chelating activity. Results showed that ethanol extracts of Rumex pulcher, A. undulata subsp. hybrida and Campanula lyrata, which were collected in edible periods exhibited the highest DPPH free radical scavenging activity and ABTS.+ scavenging activity. Moreover, Asparagus acutifolius, Galium aparine and Campanula lyrata, which were collected in edible periods exhibited the highest metal chelating activity. The results obtained from this study showed that R. pulcher, A. undulata subsp. hybrida, C. lyrata, A. acutifolius and G. aparine, which were collected in edible periods can be used as sources of natural antioxidants in food industry. © 2016, Romanian Society for Pharmaceutical Sciences. All rights reserved.
Keywords: ABTS.+; DPPH; Metal chelating; Wild edible plants